(untitled) (Scientific journal of the Fergana State University, 2023)
This article is about computer software terms in English and Uzbek, their origin, and their use. In modern English linguistics, technological terms are widely studied and large and serious research has been conducted on this theme. However, great deals of new terms are emerging in computer science every day. The terminology itself is considered one of the youngest sciences. It is enriching with the help of combining two or more words to create a new term, adding new meaning to a term or word, and acquiring new words from other foreign languages.